Screening of Some Species of Thai Microsoroid Ferns for Phytoecdysteroids - จิตตชุ่ม ดร.วรางคณา; พรหมแดง สมนึก; ทองทวี ดร.น้ำฝน; เพชรศรี ดร.สหณัฐ (Journal of Food Health and Bioenvironmental Science, 2016)
Phytochemical screening investigation in the fronds of the seven species of Thai microsoroid ferns (Polypodiaceae) resulted in the isolation of 10 significant phytoecdysteroids (PEs). These fern in the conservation area of northern Thailand were collected and compared with previously recognized taxa. In addition, M. insigne, M. punctatum, and P. scolopendria represent an excellent source of PEs. This is the pioneer work that reports the study on the screening of the PEs from the dried aerial parts of M. insigne. Unfortunately, the ecdysteroids in M. membranaceum could not be found by using HPLC because of its insolubility in this solvent system. Moreover, the variety of PEs found in Thai microsoroid ferns could not potentially be distinguished from their ferns at the genus level. The voucher specimens of the study species were deposited at the Botanical Laboratory, Science Department, Faculty of Liberal Arts and Sciences, Kasetsart University, Kamphang Saen Campus.